Lenalidomide treatment in lower risk myelodysplastic syndromes—The experience of a Czech hematology center. (Positive effect of erythropoietin ± prednisone addition to lenalidomide in refractory or relapsed patients). (June 2018) - Jonasova, Anna; Neuwirtova, Radana; Polackova, Helena; Siskova, Magda; Stopka, Tomas; Cmunt, Eduard; Belickova, Monika; Moudra, Alena; Minarik, Lubomir; Fuchs, Ota; Michalova, Kyra; Zemanova, Zuzana
Highlights: Lenalidomide is highly effective in low risk myelodysplastic syndrome with del(5q). Borderline bone marrow blasts and TP53 mutation signal a risk of progression. Addition of erythropoietin can trigger response in refractory or relapsed patients. Further improvement can be obtained with the addition of prednisone. Abstract: Lenalidomide therapy represents meaningful progress in the treatment of anemic patients with myelodysplastic syndromes with del(5q). We present our initial lenalidomide experience and the positive effect of combining erythropoietin and steroids with lenalidomide in refractory and relapsed patients. We treated by lenalidomide 55 (42 female; 13 male; median age 69) chronically transfused lower risk MDS patients with del(5q) (45) and non-del(5q) (10). Response, meaning transfusion independence (TI) lasting ≥ eight weeks, was achieved in 38 (90%) of analyzed patients with del(5q), of whom three achieved TI only by adding erythropoietin ± prednisone. Another five patients responded well to this combination when their anemia relapsed later during the treatment. In the non-del(5q) group only one patient with RARS-T reached TI. Cytogenetic response was reached in 64% (32% complete, 32% partial response). The TP53 mutation was detected in 7 (18%) patients; four patients progressed to higher grade MDS or acute myeloid leukemia (AML). All seven RAEB-1 patients cleared bone marrow blasts during lenalidomide treatment and reached complete remission (CR); however, three later progressed to higher grade MDS or AML. Lenalidomide represents effective treatment for del(5q) group and combination with prednisone and erythropoietin may be used for non-responders or therapy failures.